Benzoic and propionic acids in fishery products on the Korean market. Issue 3 (2nd July 2020) - Jang, Gwang-Ju; Yoo, Miyoung; Lee, Sanghee
ABSTRACT: A new pretreatment technique for the sensitive and accurate determination of benzoic and propionic acids in fishery products by HPLC-DAD and GC-MS was established to address the regulatory problem posed by the natural metabolic production of preservatives during food processing. A total of 786 samples (332 raw fish and 454 processed fish products) were investigated. Benzoic acid was detected in 2.4% of raw fish samples, 9.7% of processed product samples, while the corresponding numbers for propionic acid equalled 88.3% and 94.7% respectively. As are result of monitoring the samples obtained from the Korean market, propionic acid was detected in most samples, but benzoic acid was detected in some fish. These results provide fundamental data regarding naturally occurring preservatives in fishery. As a result of these databases in fishery could be used as important data for the judgement that they are naturally originated preservatives.